Psychogenic nonepileptic seizures in adult neurology clinics in southern Iran: A survey of neurologists - Asadi-Pooya, Ali (Iran J Neurol, 2016)
Background: We investigated the perceptions of the neurologists practicing in Fars province in Southern Iran about psychogenic nonepileptic seizures (PNES); their diagnostic processes and management strategies. Methods: In this survey, all neurologists participating at the annual meeting of neurologists were asked to participate. These neurologists practice in Fars province. An anonymous questionnaire was specifically developed for this study. Results: About 18 neurologists (14 males and four females), out of 20 attendees, agreed to participate in the study. The mean age of the participants was 41.6 ± 7.5 years. They estimated that 10.8% of patients attending their clinic had seizures or blackouts, whereas 4.4% of patients attending their clinic had PNES. The experiences of the participants about the manifestations that potentially differentiate PNES from epileptic seizures; the tests they use to diagnose suspected patients and their treatment strategies showed significant variability. For example, the tests the neurologists always used for the diagnosis of PNES in suspected patients included routine electroencephalographs (EEGs) by 9 (50%), video-EEG monitoring by 4 (22%), and serum creatine phosphokinase (CPK) measurement by 2 (11%). Conclusion: There is much variability in the approaches to diagnosis and management of PNES in southern Iran. The participants in our study were aware of the many knowledge gaps in this area.